STARTING A NEW BUSINESS FOR GENERATION Z IN INDONESIA: ENTREPRENEURIAL MOTIVATION IN THE TOURISM AND HOSPITALITY INDUSTRY - Debry C. A. Lintong; Jeffry L. A. Tampenawas; Raymond Ch. Kawet; Christoffel M. O. Mintardjo; Imelda W. J. Ogi (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2026)
Youth entrepreneurship is increasingly recognized as an important driver of economic growth, job creation, and regional competitiveness. This study aims to examine the effects of entrepreneurial environment, self-confidence, and entrepreneurial motivation on the entrepreneurial intention of Generation Z to start a business in the tourism and hospitality sector in Manado City. The study employed a quantitative approach with an explanatory survey design. Primary data were collected through structured questionnaires administered to 250 Generation Z respondents in Manado City. The data were analyzed using multiple linear regression with partial and simultaneous hypothesis testing. The results show that entrepreneurial environment, self-confidence, and entrepreneurial motivation have positive and significant effects on entrepreneurial intention. Simultaneously, the three variables provide a substantial explanation for entrepreneurial intention in the tourism and hospitality sector. These findings indicate that Generation Z tends to develop stronger entrepreneurial intention when they are situated in a supportive ecosystem, possess confidence in their own capabilities, and are driven by meaningful goals such as financial independence, self-actualization, and social contribution. This   Keywords: Entrepreneurial Motivation, Generation Z, Entrepreneurial Intention, Tourism, Hospitality